High Cognitive Activation Strategy Boosts Students' Math Achievement and Self-Efficacy: Strategi Aktivasi Kognitif Tinggi Meningkatkan Prestasi Matematika dan Efikasi Diri Siswa - Hajj, Mustafa Raheem (Indonesian Journal of Education Methods Development, 2024)
General Background: Mathematics education plays a critical role in shaping students' cognitive abilities and self-efficacy. Effective instructional strategies are essential to enhance learning outcomes and foster students' confidence in mathematical problem-solving. Specific Background: Traditional teaching methods often fail to engage students in higher-order thinking, limiting their ability to develop deep mathematical understanding. The "High Cognitive Activation" strategy has emerged as a promising approach to enhance student engagement and achievement. Knowledge Gap: While previous research has explored various active learning strategies, limited studies have examined the impact of high cognitive activation on both mathematical achievement and self-efficacy among preparatory students. Aims: This study investigates the effectiveness of the High Cognitive Activation strategy on the achievement and mathematical self-efficacy of fourth-grade scientific students in Baghdad. Results: A quasi-experimental design was implemented with 77 students, divided into experimental and control groups. Findings revealed that students taught using the High Cognitive Activation strategy significantly outperformed those taught using conventional methods in both achievement and self-efficacy. Novelty: This research provides empirical evidence supporting the effectiveness of high cognitive activation in mathematics education, highlighting its role in fostering deep learning and self-confidence. Implications: The findings suggest integrating high cognitive activation strategies into mathematics curricula to enhance students’ learning experiences and motivation, ultimately improving educational outcomes. Highlights: Investigate high cognitive activation’s impact on math achievement and self-efficacy. Improved achievement and self-efficacy in the experimental group. Supports active learning integration in mathematics education. Keywords: High Cognitive Activation Strategy, Mathematical self-efficacy.